Mesh Stiffness Modelling and Dynamic Response Analysis of Spur Gear Pair with Assembly Error and Tooth Surface Friction - Nie Li; Xu Zhiliang; Xu Huachao (Jixie chuandong)
To explore the meshing and dynamic evolution of spur gear pairs under the combined influence of assembly errors and tooth surface friction, a method integrating geometric analysis of spur gear pairs with energy method was employed. The impact of assembly errors and tooth surface friction on spur gear pair meshing was investigated. A 6-degree-of-freedom bending-torsional coupling vibration model of spur gears was established based on the lumped mass method. Numerical solutions characterizing the meshing behavior and dynamic response of the system were obtained using the Runge-Kutta method. The analysis reveals that, the mesh stiffness amplitude of the spur gear pair decreases with the increase of the tooth surface friction coefficient. Additionally, simulation results demonstrate that appropriately adjusting the installation conditions and using reasonable tooth surface friction coefficients of spur gear pairs can improve its transmission accuracy and vibration characteristics. The research findings can provide references for the dynamic analysis of spur gear transmission systems under the influence of systematic errors.